2012
DOI: 10.1002/jib.20
|View full text |Cite
|
Sign up to set email alerts
|

HS-SPME/GC-MS and chemometrics for volatile composition of Chinese traditional aromatic vinegar in the Zhenjiang region

Abstract: The main purpose of this study was to determine the volatile composition of Zhenjiang aromatic vinegar, one of the four famous China-style cereal vinegars, by using headspace solid-phase microextraction (HS-SPME)/gas chromatography-mass spectrum (GC-MS) and chemometrics. For this purpose, the HS-SPME sampling method for the volatile compounds of Zhenjiang aromatic vinegar was optimized by a second-order rotatable central composite experimental design (CCD). A HS extraction of the volatile compounds by incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 49 publications
(59 reference statements)
3
49
0
Order By: Relevance
“…GV are characterized by vanillic acid, gallic acid, tyrosol, protocatechuic acid, caftaric acid, coutaric acid, ferulic acid, fertaric acid, syringic acid, procyanidin B2, catechin, epicatechin, quercetin‐3‐ O ‐galactoside, kaempferol‐3‐ O ‐rutinoside, isorhamnetin 3‐glucoside and quercetin. In the study reported by Yu et al , PCA was applied for discrimination and characterization of Zhenjiang aromatic vinegars according to their volatile compounds analysed using headspace solid‐phase microextraction/gas chromatography–mass spectrometry. Nine alcohols, 13 acids, 16 esters, five aldehydes, four ketones and eight heterocycle compounds were identified in the samples.…”
Section: Resultsmentioning
confidence: 99%
“…GV are characterized by vanillic acid, gallic acid, tyrosol, protocatechuic acid, caftaric acid, coutaric acid, ferulic acid, fertaric acid, syringic acid, procyanidin B2, catechin, epicatechin, quercetin‐3‐ O ‐galactoside, kaempferol‐3‐ O ‐rutinoside, isorhamnetin 3‐glucoside and quercetin. In the study reported by Yu et al , PCA was applied for discrimination and characterization of Zhenjiang aromatic vinegars according to their volatile compounds analysed using headspace solid‐phase microextraction/gas chromatography–mass spectrometry. Nine alcohols, 13 acids, 16 esters, five aldehydes, four ketones and eight heterocycle compounds were identified in the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Main component contributing to the negative loadings is caramel, because those variables are spread across the line loading plots with broad line width. One the other hand, resonances with high positive PC2 values are ethanol (7), ethyl acetate (8), succinate (18), malate (17), citrate (34), fructose (22), β-glucose (25) and α-glucose (26). One the other hand, resonances with high positive PC2 values are ethanol (7), ethyl acetate (8), succinate (18), malate (17), citrate (34), fructose (22), β-glucose (25) and α-glucose (26).…”
Section: Comparison Of Chinese Cereal Vinegars With European Grape VImentioning
confidence: 99%
“…[2] In Europe, most commercial vinegars are made from grape such as wine vinegar and Balsamic vinegar of Modena (BVM). [8][9][10][11][12][13][14][15][16][17] Mass spectrometry combined with SNIF-NMR methods has been used for authentication of natural vinegar by detecting carbon or hydrogen isotope fractionation of acetate. [3][4][5][6] BVM is another type of commercial-grade grape vinegar blending from cooked must and wine vinegar.…”
Section: Introductionmentioning
confidence: 99%
“…This sample extraction technique was demonstrated to be rapid, simple, and reproducible, with no solvent use, and is suitable for the extraction and concentration of a high number of volatile and semi-volatile compounds from aqueous solutions (Yu et al, 2012). Analyses were conducted using HS-SPME technique followed by gas chromatography coupled with a flame ionization detector (GC-FID), 50/30 μm divinylbenzene/carboxen/ polydimethylsiloxane (DVB/CAR/PDMS) fiber.…”
Section: Chemistry Analysis and Reagentsmentioning
confidence: 99%